Onmyouji dan Peranan nya dalam Masyarakat Jepang di Tokyo Raven - Made Bramantya Yoga Saputra Made Bramantya Yoga Saputra; Wayan Nurita (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2026)
This study aims to describe Onmyouji and its role in Japanese society. This type of research is descriptive-qualitative. The data source used in this study is the Anime "Tokyo Ravens". Data collection methods and techniques in this study used the listening method with advanced note-taking techniques, namely by listening to the anime "Tokyo Raven" then noting what the roles of Onmyouji in Japanese society were in the anime "Tokyo Ravens" and studying the formal technique method, namely analyzing data. by using pictures. The results of the study show that Onmyouji has a unique role for Japanese society.